GSK3β Plays a Negative Role During White Spot Syndrome Virus (WSSV) Infection by Regulating NF-κB Activity in Shrimp Litopenaeus vannamei - Zhang, Shuang; Zhu, Lulu; Hou, Cuihong; Yuan, Hang; Yang, Sheng; Dehwah, Mustafa Abdo Saif; Shi, Lili (Frontiers in Immunology, 2020)
Glycogen synthase kinase-3 (GSK3), a cytoplasmic serine/threonine-protein kinase involved in a large number of key cellular processes, is a little-known signaling molecule in virus study. In this study, a GSK3 protein which was highly similar to GSK3β homologs from other species in Litopenaeus vannamei (designated as LvGSK3β) was obtained. LvGSK3β was expressed constitutively in the healthy L. vannamei, at the highest level in the intestine and the lowest level in the eyestalk. White spot syndrome virus (WSSV) reduced LvGSK3β expression was in immune tissues including the hemocyte, intestine, gill and hepatopancreas. The inhibition of LvGSK3β resulted in significantly higher survival rates of L. vannamei during WSSV infection than the control group, and significantly lower WSSV viral loads in LvGSK3β-inhibited L. vannamei were observed. Knockdown of LvGSK3β by RNAi resulted in increases in the expression of LvDorsal and several NF-κB driven antimicrobial peptide (AMP) genes (including ALF, PEN and crustin), but a decrease in LvCactus expression. Accordingly, overexpression of LvGSK3β could reduce the promoter activity of LvDorsal and several AMPs, while the promoter activity of LvCactus was increased. Electrophoretic mobility shift assays (EMSA) showed that LvDorsal could bind to the promoter of LvGSK3β. The interaction between LvGSK3β and LvDorsal or LvCactus was confirmed using co-immunoprecipitation (Co-IP) assays. In addition, the expression of LvGSK3β was dramatically reduced by knockdown of LvDorsal. In summary, the results presented in this study indicated that LvGSK3β had a negative effect on L. vannamei by mediating a feedback regulation of the NF-κB pathway when it is infected by WSSV.